Visionary Leadership In Promoting Islamic Values In Schools: A Phenomenological Study At SDN 1 Durenan Trenggalek - Winarto, Winarto; Suyitno, Suyitno; Zahria, Linta (International Journal of Science and Environment (IJSE), 2025)
As a form of responsibility toward transformation in the field of education, schools must have the capacity to realize and develop students’ character by strengthening the role of religion in learning activities. Religious activities not only play a crucial role in shaping student character but also foster habits of discipline, responsibility, and the development of good personal values. Discipline, in turn, leads to orderly learning, which becomes a motivation for academic achievement. A visionary principal holds a strategic role in encouraging students to develop religious character through various religious activities conducted by the school, including extracurricular, intramural, and co-curricular programs. This study employs a qualitative method with a phenomenological design. Data were collected through interviews, observations, and documentation. The data analysis technique follows the Miles and Huberman model, including data display, data reduction, and data verification (drawing conclusions). Visionary leadership in developing Islamic values at SDN 1 Durenan, Trenggalek, is implemented massively through religious activities. The principal plays a central role as a leader of change, policy-maker, and coordinator in improving students’ academic achievement. As agents of change, educators and school staff are responsible for implementing and evaluating religious activities in the school environment. Students, as the primary focus of academic achievement improvement, receive full attention from both the principal and the teaching staff.